2019
DOI: 10.1089/mab.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Natural Killer and CD8+T Cell-Mediated Anticancer Cytotoxicity and Proliferation of CD8+T Cells with HLA-E Monospecific Monoclonal Antibodies

Abstract: Cytotoxic NK/CD8 + T cells interact with MHC-I ligands on tumor cells through either activating or inhibiting receptors. One of the inhibitory receptors is CD94/NKG2A. The NK/CD8 + T cell cytotoxic capability is lost when tumor-associated human leukocyte antigen, HLA-E, binds the CD94/NKG2A receptor, resulting in tumor progression and reduced survival. Failure of cancer patients to respond to natural killer (NK) cell therapies could be due to HLA-E overexpression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 123 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…As a non-classical major histocompatibility complex (MHC) molecule, HLA-E can interact with NK cells and T cells (15,16). It has been suggested that the overexpression of HLA-E on cells could inhibit the immune clearance function (17). On some tumors, including MM, inflammatory cells and senescent cells with highly expressed HLA-E could escape the NK and T-cell immune surveillance and stay alive in the host body (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…As a non-classical major histocompatibility complex (MHC) molecule, HLA-E can interact with NK cells and T cells (15,16). It has been suggested that the overexpression of HLA-E on cells could inhibit the immune clearance function (17). On some tumors, including MM, inflammatory cells and senescent cells with highly expressed HLA-E could escape the NK and T-cell immune surveillance and stay alive in the host body (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…These receptors can bind to specific ligands, mainly the major histocompatibility complex class (MHC-1) that is expressed on healthy hepatocytes, which interacts with inhibitory receptors on NK cells and prevents the activation of NK cells. The inhibitory Killer Ig-like receptors (KIRs) that recognize classical MHC-I alleles and the C-type lectin like receptor NKG2A that forms a heterodimer with the CD94 molecule (CD94/NKG2A) and bind HLA-E, a non-classical MHC-I molecule prevent NK cell activation (Figure 1A) [70]. During viral infection, hepatocytes upregulate stimulatory ligands for NK cell activating receptor NKG2D and as a result activation signal surpasses signaling through the inhibitory receptors KIRS and NKG2A, resulting in cytokine release and cytolysis of target cells (Figure 1B).…”
Section: Nk Cells and Immune Surveillancementioning
confidence: 99%
“…NK cells can thus directly eradicate infected cells or tumor cells lacking MHC-1 molecule expression [55]. Therefore, approaches to regulate the balance between activating and inhibitory receptors in NK cells, might also lead to the successful treatment for various liver diseases including HCC [70,72]. Hepatocarcinoma cells express ligands of several activating NK receptors (NKR), including NKp30, natural killer receptor group 2, member D (NKG2D), and DNAM-1, such as the B7 protein homolog 6, the major histocompatibility complex class I chain-related protein A and B (MICA/B), and CD155, respectively, whose expression can correlate with HCC outcome [73,74].…”
Section: Nk Cells and Immune Surveillancementioning
confidence: 99%
“…Human ECs and several leukocytes, including DCs, express HLA-E on their surface, which is upregulated by proinflammatory cytokines ( 90 , 91 ). HLA-E primarily functions as the specific ligand for an inhibitory receptor (CD94/NKG2A) on NK and CD8+ T cells ( 92 ) ( Figure 1A ). Examining the effects of the presence or absence of HLA-E on the surface of CD94/NKG2A positive NK Cell line (LCL.221-AEH), inhibition of NK cell-mediated cytolysis by HLA-E was documented.…”
Section: Allograft-associated Immune Cells Respond To Inflammation: Double Immune Reaction Host- Versus -Graft and Gramentioning
confidence: 99%